Atypical Lung Parenchymal Bronchogenic Cyst Complicated by Tuberculosis Infection. Issue 5 (2012) - Chu, Haiqing; Yi, Xianghua; Zhao, Lan; Gui, Tao; Fang, Xia; Sun, Xiwen
Abstract : A bronchogenic cyst (BC) is a rare congenital lesion that may cause life-threatening organ compression in children, but is generally asymptomatic in adults unless there are other complications. In the present report, a 34-year-old woman in whom a BC was complicated by tuberculosis infection is described. Due to the small size of the BC, it was asymptomatic and could not be diagnosed until she was treated with antituberculosis medications.